COMPARATIVE ANALYSIS OF LETTERS IN THE UZBEK AND ARABIC ALPHABETS - Yodgorova Diyora Jo‘rabek qizi (Modern American Journals, 2025)
This article provides a comprehensive overview of the historical development of the Uzbek script, tracing the transition from Arabic script to Cyrillic, and subsequently to the current Latin alphabet. It also presents a comparative analysis of the phonetic capabilities of Uzbek letters, the distinctive features, and shortcomings of various writing systems. The study draws scientific conclusions based on historical sources, linguistic scholars’ opinions, and practical challenges.
Keywords: history of Uzbek script, Arabic script, Cyrillic script, Latin script, phonetic capabilities, comparative analysis of writing systems, alphabet reform.